2020
DOI: 10.1177/1465116520938148
|View full text |Cite
|
Sign up to set email alerts
|

Do Spitzenkandidaten really make a difference? An experiment on the effectiveness of personalized European Parliament election campaigns

Abstract: This article investigates the impact of pan-European candidates in European Parliament election campaigns. It focusses on the two 2019 nominees for the European Greens, who were Dutch and German, respectively. We conducted a pre-registered experiment in the Netherlands and Germany in early April 2019 to test the effects of (non-)personalized campaign posters on (a) turnout intention and (b) vote intention for the Greens alongside possible mediating effects of campaign and candidate evaluations. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…The aim of the Spitzenkandidaten procedure was to raise voter awareness and participation. However, evidence suggests that their impact on electoral behaviour has been rather mixed (Gattermann and Marquart, 2020; Schmitt et al, 2015). The purpose of this contribution was to study this phenomenon against the backdrop of mediated personalization processes during EP elections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the Spitzenkandidaten procedure was to raise voter awareness and participation. However, evidence suggests that their impact on electoral behaviour has been rather mixed (Gattermann and Marquart, 2020; Schmitt et al, 2015). The purpose of this contribution was to study this phenomenon against the backdrop of mediated personalization processes during EP elections.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a favourable condition for personalized voting behaviour, although a preliminary empirical assessment showed that it mainly occurs among sophisticated voters and that party preferences still play a more decisive role compared to candidate evaluations (Gattermann and de Vreese, 2017). Likewise, few voters actually recognize Spitzenkandidaten (Hobolt, 2014) and thus their impact on voter turnout and vote intention is somewhat limited (Schmitt et al, 2015; Gattermann and Marquart, 2020). This may also indicate that media coverage of EP election campaigns as main source of information for voters is not very personalized (see Belluati, 2016: Schulze, 2016).…”
Section: Why Mediated Personalization Of European Elections?mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the authors, voters also felt more informed about the issues discussed during the debate; there are also weak indications that some changed their positions towards certain issues after having followed the debate. This suggests that the Spitzenkandidaten can add a distinct European perspective to the campaigns in combination with policy issues, although there is mixed evidence for the extent to which they indeed mobilise voters across Europe (Gattermann and Marquart, 2020; Schmitt et al, 2015).…”
Section: Campaigning and Mobilisation At A Pan-european Levelmentioning
confidence: 99%